Bioactive Compounds Incorporation into the Production of Functional Biodegradable Films - A Review. Issue 4 (November 2017) - Luchese, Cláudia Leites; Brum, Luis Fernando Wentz; Piovesana, Alessandra; Caetano, Karine; Flôres, Simone Hickmann
The bioactive compounds incorporation for the production of biodegradable food packagings comes as a viable and environmentally friendly substitute in order to improve the nutritional value as well as extend the shelf life of highly perishable food products. Moreover, the use of bioactive compounds has been directly associated with the promotion of health aspects; the ingestion of bioactive compounds is related with minimizing risks of some diseases such as hypertension, diabetes, and coronary heart diseases. Therefore, the present study carried out a review of the current scenario in the film's production with natural antioxidants addition. The prebiotics and probiotics compound addition in films properties produced were also discussed in this work. Additionally, the film biodegradation properties should also be taken into account for their right disposal in the environment. Some factors that can to affect the biodegradation process are the nature of the polymer, the interactions among the blend components, its crystallinity, and the environmental conditions (light, temperature, O2 concentrations; and humidity). Therefore, the evaluation of relationships between structure and the polymers biodegradability is the extreme importance.